KELAYAKAN MAJALAH SEBAGAI BAHAN PENGAYAAN PADA SUBMATERI KEANEKARAGAMAN GEN, JENIS, EKOSISTEM KELAS X SMA - Nurhuda, Nurhuda; Syamswisna, Syamswisna; Tenriawaru, Andi Besse (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the feasibility of magazine media on the sub-material of gene, species, and ecosystem diversity. The method used in this research is descriptive quantitative. The magazines that have been created will then be validated and analyzed using Content Validity Ratio (CVR) analysis which refers to Lawshe (1975). The media validator consists of five people who were selected by purposive sampling with the consideration that they are considered capable of providing a good assessment. Two validators are biology education lecturers at the Faculty of Education, Tanjungpura University, and three other validators, namely class X biology teachers at SMA Negeri 1 Sungai Kakap, SMA Negeri 2 Sungai Kakap, and SMA Negeri 3 Sungai Kakap. Based on the results of the validation analysis, the magazine media has been validated to be suitable for use as a material introduction media with a CVR value of 1.00 which means that the magazine media is valid.